Enzyme histochemical study of primary hepatic carcinoma in thailand - Tinrat Stitnimankarn (2018)
A histochemical study of a number of hydrolytic and oxidative enzymes was made on 29 surgical biopsy and 15 postmortem specimens of primary hepatic carcinoma. Alkaline phosphatase could not be demonstrated in tumor tissue from any of the 44 cases studied. Lactate and isocitric dehydrogenases, and DPNH‐diaphorase showed greater intensities of reaction in a majority of the tumors as compared with nontumorous parenchyma on the same slides. Enzyme reactions appeared to be greater in the liver tissue than in the tumor nodules in a majority of cases for glucose‐6‐phosphate, glutamate, beta‐hydroxybutyric, and 6‐phosphogluconate dehydrogenases. This difference was most prominent in the last 2 enzymes. Dihydro‐orotate dehydrogenase and TPNH‐diaphorase gave variable results. Similar results were obtained in both surgical biopsy and postmortem specimens. No consistent differences in the reactions of the tumor tissues were observed in relation to the presence or absence of cirrhosis. Enzymatic activities of carcinomas of the liver were not related with the morphological grade of differentiation. Copyright © 1969 American Cancer Society